Outcome of and Prognostic Factors for Herpes Simplex Encephalitis in Adult Patients: Results of a Multicenter Study - Raschilas, Franck; Wolff, Michel; Delatour, Frédérique; Chaffaut, Cendrine; De Broucker, Thomas; Chevret, Sylvie; Lebon, Pierre; Canton, Philippe; Rozenberg, Flore (Clinical infectious diseases, 2002)
Management of herpes simplex encephalitis (HSE) has been considerably improved by the availability of acyclovir therapy and rapid polymerase chain reaction (PCR)—based diagnostic assays. Prognostic factors for this rare affliction are, however, misestimated. We conducted a large retrospective multicenter study that included 93 adult patients in whom HSE was diagnosed by PCR from 1991 through 1998 and who were treated with intravenous acyclovir. Among the 85 patients assessed at 6 months, 30 (35%) had a poor outcome, which led to death in 13 patients (15%) and severe disability in 17 (20%). The outcome was favorable for 55 patients (65%). A multivariate analysis identified 2 factors that were found to be independently associated with poor outcome: a Simplified Acute Physiology Score II ⩾27 at admission and a delay of >2 days between admission to the hospital and initiation of acyclovir therapy. Early administration of antiviral therapy is the only parameter that can be modified to improve the prognosis of patients with HSE.